Types of child abuse in the UAE society: qualitative study - Almarzouqi, Fatima; Algharaibeh, Fakir (Al-Adab Journal, 2024)
This research aims to study the types of abuse committed against children in UAE society, specifically in the emirates of Dubai and Sharjah, where it shed light on a purposive sample consisting of 22 male and female children whose abuse required them to be placed in shelters affiliated with the Children and Women’s Care Foundation in Dubai and the Social Welfare Home affiliated with the Department. Social services in Sharjah. The researcher used the qualitative approach, specifically the case study approach, through in-depth study of case files and interviewing case managers. The study focused on identifying the type of abuse occurring. Emotional abuse occupied first place, especially since its occurrence coincided with other abuses and was not the only reason for the child’s admission to the shelter center, followed by abuse and neglect. Then there is physical abuse, the last of which is sexual abuse. The study focused on the types of therapeutic programs provided to the victim within the shelter center to help the victim get rid of the effects of the assault and help them towards integration into society.